Germline large deletion of BAP1 and decreased expression in non‐tumor choroid in uveal melanoma patients with high risk for inherited cancer. Issue 9 (23rd April 2019) - Boru, Getachew; Grosel, Timothy W.; Pilarski, Robert; Stautberg, Meredith; Massengill, James B.; Jeter, Joanne; Singh, Arun; Marino, Meghan J.; McElroy, Joseph P.; Davidorf, Frederick H.; Cebulla, Colleen M.; Abdel‐Rahman, Mohamed H.
Abstract: Uveal melanoma (UM) is the most common phenotype in patients with germline BAP1 mutation. This study aimed to identify selection criteria for BAP1 germline testing and assessed the role of large deletion/duplication and epigenetic inactivation. One hundred seventy‐two UM patients with high risk of hereditary cancer were included. Germline variants in BAP1 were assessed by direct sequencing and large deletion/duplication by multiplex ligation‐dependent probe amplification. BAP1 expression in unaffected choroid tissue from a patient with UM was assessed by quantitative RT‐PCR and methylation by pyrosequencing. Twenty‐eight patients had one or more germline sequence variants in BAP1 ; seven of these were pathogenic. One hundred forty patients were assessed for large deletion/duplication and in one BAP1 whole gene deletion was detected. In total, eight patients (4.7%) had pathogenic alterations in BAP1 with the highest frequencies of in patients with a personal/family history of ≥2 BAP1‐ related cancers 6/16 (38%), age of onset <35 years 4/21 (19%) and familial UM 6/34 (18%). One of 19 non‐tumor choroid tissues tested showed uncharacteristically low expression as compared to the controls decrease in BAP1 RNA expression but no evidence of constitutional promotor hypermethylation was detected. UM patients with a strong personal or family history of cancers associated with BAP1, early age of onset and familial UM should be assessed for germline variants in BAP1, including large deletions.